Collaboration results in higher impact research: Case study of the Canadian Forest Service - Heather MacDonald; Kaitlin DeBoer; Daniel W. McKenney (The Forestry Chronicle, 2023)
The Canadian Forest Service (CFS) has a mandate to share its full breadth of scientific knowledge concerning Canada’s forests broadly, with citizens, as well as narrowly, with organizations responsible for managing forests. Measuring the impact of CFS research in policy-making both nationally and internationally can be challenging, as policies may not reference research contributing to decisions. This paper presents an analysis of how collaboration with different partners impacts the reach of CFS research, as measured by published citation databases. We found that CFS publications authored or co-authored with a U.S. or Canadian federal government author had significantly higher research impact. University co-authorship also increased impact, in part through the quality of publication journals.